Improving parathyroid preservation in thyroidectomy: The case for near-infrared autofluorescence guidance - Azam, Abdullah; Rizvi, Faaiz; Khan, Ushna (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Thyroidectomy, once banned by the French medical society in 1850, is now a widely performed procedure. It is indicated for various thyroid pathologies, including thyroid cancer, Hurthle cell tumours, and large goiter’s that cause compressive symptoms. Furthermore, thyroidectomies are also carried out as per patient preference for aesthetic purposes. Patients undergoing thyroidectomy can have both major and minor complications. Minor complications include seroma formation at the wound site and wound scarring. Major complications include postoperative bleeding, recurrent laryngeal nerve damage leading to dysphonia and hypoparathyroidism. (1) Hypoparathyroidism is the most common complication of thyroidectomy. There is a reported incidence of transient hypoparathyroidism ranging from 19% to 38% and of permanent hypoparathyroidism from 0% to 3%. Hypoparathyroidism can occur due to the accidental dissection of the parathyroid glands intraoperatively. Parathyroid glands are small in size and have a similar colour to the surrounding cervical tissue, making it difficult to differentiate them. Hypoparathyroidism commonly presents with symptoms such as paraesthesia of the perioral region and fingertips. Hypoparathyroidism commonly presents with symptoms such as paraesthesia of the perioral region and fingertips. It can also present with neuropsychiatric manifestations, including anger and confusion. Physical examination findings may include Chvostek’s sign (facial muscle contraction on tapping the preauricular region) and Trousseau’s sign (carpopedal spasm induced by occluding the brachial artery with a blood pressure cuff) Recently, a new technique has been developed for enhanced intraoperative detection of parathyroid glands called near-infrared autofluorescence (NIRAF) imaging. (2) A meta-analysis published in 2022 provided corroborating evidence by pooling data from eight studies comparing NIRAF to standard naked-eye surgery. The incidence of transient hypoparathyroidism in the NIRAF group was 28.31% compared to 33.36% in those undergoing standard naked-eye surgery, a statistically significant reduction (p = 0.0008). Furthermore, the rate of inadvertent parathyroid gland resection was significantly lower in the NIRAF group by 6.74% (7.65% vs. 14.39%, p < 0.0001) (3) Pakistan has a struggling healthcare system with limited hospitals and resources. (4) In light of these shortcomings, it is imperative that surgeons adopt techniques that minimise postoperative complications and follow-up visits. The authors suggest implementing NIRAF imaging during thyroidectomies. NIRAF imaging has been reported to reduce the incidence of transient hypocalcaemia, which will decrease the need for prolonged hospitalisation. Additionally, by improving surgical outcomes, NIRAF imaging will enhance the public trust in healthcare professionals, discouraging patients from seeking treatment from unqualified practitioners.